VD_FINDINFO Arrêt / 2013 / 498 vom 4. Juli 2013 - VD Tribunal cantonal (2013)
CURATELLE DE GESTION, CURATELLE DE REPRÉSENTATION, PROSTITUTION | 390 al. 1 ch. 1 CC, 145 al. 1 CPC (CH), 145 al. 2 let. b CPC (CH), 145 al. 3 CPC (CH), 148 CPC (CH)